Le détachement en position initiale: rôle phrastique ou discursif/textuel? Exemple du syntagme à propos de X - Porhiel, Sylvie (Linguistik Online, 2006)
The syntagm à propos de X can syntactically function two ways: on a cline from left to right, one goes from no integration (with the indexation of à propos de X; it has a thematic reading and is a marker of thematization) towards a maximum integration (when the syntagm depends on another morphosyntactic element; it has an ’about’, a causal or a temporal reading and is not a marker of thematization). This integrative scale allows hypothesizing that indexing à propos de X against the remaining proposition gives this syntagm a textual function as it provides an interpretative background for the proposition. Within the sentence, analysis suggests it is difficult to index à propos de X. However, analysis also shows that indexing à propos de X is possible when providing sentences, where à propos de X is integrated, with a context and when indexing this syntagm. A textual perspective modifies the grammatical judgments made in the sentence, makes the examples sufficient and also underlines that the maker of thematization à propos de X is potentially integrative and oppositive. The detachment of à propos de X does not mean however that the syntagm is systematically a thematic introducer. To determine when it is the case in examples where i) à propos de X is detached and ii) where a noun, a verb or an adjective combines with a complement, this paper introduces a saturation principle.